(untitled) (Sport Science Research, 2025)
The relevance of this study lies in the circumstances under which students, working with electronic educational resources, must possess specific knowledge and skills for their effective implementation. In practice, both students and educators encounter the following issues. Students need to understand and be capable of interacting with learners in their professional activities when delivering volleyball program material using an electronic textbook. For educators, their professional activity should follow a sequential approach to foster these competencies in the student learners. The main idea of this work is to identify methodological approaches for developing students’ competencies in solving informational and communicative problems during the use of an electronic volleyball textbook. The conducted study defines the criteria and stages for the formation of the examined competencies, presents an algorithm for working with the electronic textbook aimed at developing these competencies, and identifies the initial level of their formation. The validity of the proposed methods for competency development has been confirmed. Following the experimental intervention, positive changes were observed: in the research group, the proportion of competencies at the first stage decreased from 54.4% to 15.4%, at the second stage increased from 42.6% to 74.2%, and at the third stage rose from 5% to 10.4%.